ANALISIS PERBANDINGAN ARTIKEL TENTANG EFEKTIVITAS PERMAINAN MENCOCOKKAN KATA BAHASA LAMPUNG TERHADAP PENGUASAAN KOSAKATA SISWA - Fadilah, Bagus Adi; Sari, Nabila Diana (STKIP Pesisir Selatan, 2025)
This study aims to analyze and compare the effectiveness of the word-matching game in enhancing students’ vocabulary mastery within the context of language learning, focusing on its implementation in both the Lampung and Indonesian languages. Two primary articles served as the basis for comparison: the study by Ika Tazkiah et al. (2025), which examined the impact of the word-matching game on elementary students’ Indonesian vocabulary acquisition, and an article from J-Simbol: Jurnal Magister Pendidikan Bahasa dan Sastra Indonesia that explored a similar approach in the context of a regional language. The analysis employed a comparative qualitative method using content analysis and thematic analysis of the methodology, findings, and novelty of both studies, supported by related literature such as Ramadhania & Yamin (2022), Muliana & Warmansyah (2022), and Utami & Bashofi (2023). The results indicate that the word-matching game has a significant effect on improving students’ vocabulary mastery, primarily due to its interactive nature, which promotes engagement and retention of new words. However, the main distinction lies in the linguistic and media contexts: Tazkiah’s study utilized the web-based Wordwall platform, while the local Lampung study emphasized cultural visualization through traditional symbols.